2012
DOI: 10.1111/j.1365-2648.2012.06088.x
|View full text |Cite
|
Sign up to set email alerts
|

The dissonant care management of illicit drug users in medical wards, the views of nurses and patients: a grounded theory study

Abstract: Aims The aim of this study was to explore how registered nurses manage and deliver care to patients admitted to medical wards and Medical Assessment Units with complications of drug use and to elicit the experiences and views of those receiving that care. Background Illicit drug use is a major public health problem worldwide. The physical complications of problem drug use often result in admission to medical wards. Registered nurses working in these settings have been reported as possessing negative attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 28 publications
4
43
1
12
Order By: Relevance
“…In dealing with patients who have an addiction, there's often an underlying false assumption of con trollability. 32,34,35 According to Monks and colleagues, this personal experience may help nurses "see the person behind the patient." 32 Similarly, Kelly and Westerhoff draw parallels between per ceived controllability and blame.…”
Section: Attitudes Toward Patients With Oudmentioning
confidence: 99%
See 1 more Smart Citation
“…In dealing with patients who have an addiction, there's often an underlying false assumption of con trollability. 32,34,35 According to Monks and colleagues, this personal experience may help nurses "see the person behind the patient." 32 Similarly, Kelly and Westerhoff draw parallels between per ceived controllability and blame.…”
Section: Attitudes Toward Patients With Oudmentioning
confidence: 99%
“…A systematic review by van Boekel and colleagues found that "high perceived controllability over a disease cause[s] more intolerant judgments and attitudes towards [that] disease." 35 Working in a psychiatric setting is also associated with more positive and nuanced atti tudes toward patients with OUD. 33 Personal exposure to substance use disorders among friends or fam ily members appears in many cases to be associated with a higher regard for patients with OUD.…”
Section: Attitudes Toward Patients With Oudmentioning
confidence: 99%
“…While higher regard for this client groups was reported in those with more frequent contact (Chu & Galang, 2013;Kelleher & Cotter, 2008;Howard & Holmshaw, 2010;van Boekel, Brouwers, van Weeghel & Garretsen, 2014) and formal training (Adams, 2008;Ford, 2010;Happell et al, 2002;Harling & Turner, 2012;Kelleher & Cotter, 2008;Lovi & Barr, 2009;Morgan, 2006), a lack of knowledge, related to limited education and training, was still seen as a major barrier to providing adequate care to PWSUD, even for specialty providers (Adams, 2008;Ford, 2010;Ford, Bammer & Becker, 2009;Kelleher & Cotter, 2008;Happell et al, 2002;Lovi & Barr, 2009;Monks, Topping & Newell, 2012). Some have related this deficit to a lack of related content in pre-registration education curricula (Harling & Turner, 2012;Howard and Holmshaw, 2010;Lovi & Barr, 2009;Kelleher & Cotter, 2008;Monks et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is important background information for the investigation of nurses' experiences caring for PWSUD for comparison with the results of my study. Five qualitative studies were captured that related to this theme: a grounded theory study by Monks et al (2012); a cross sectional study by Ford (2011); a grounded study by Morgan (2006); a phenomenological study by Lovi and Barr (2009); and a qualitative study by Spence et al (2008). These will now be discussed.…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation